2023
DOI: 10.3389/fgene.2023.1107614
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis to identify novel ceRNA regulatory axes associated with gallbladder cancer

Abstract: Competitive endogenous RNA (ceRNA) networks are reported to play a crucial role in regulating cancer-associated genes. Identification of novel ceRNA networks in gallbladder cancer (GBC) may improve the understanding of its pathogenesis and might yield useful leads on potential therapeutic targets for GBC. For this, a literature survey was done to identify differentially expressed lncRNAs (DELs), miRNAs (DEMs), mRNAs (DEGs) and proteins (DEPs) in GBC. Ingenuity pathway analysis (IPA) using DEMs, DEGs and DEPs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Meanwhile, high expression of MTDH was associated with distant metastasis of colorectal cancer and survival of patients after surgery. Moreover, based on clinical patient samples, a large number of studies have found that high expression of MTDH was significantly associated with postoperative survival rate, tumor metastasis, clinical stage progression and tumor angiogenesis in HCC 73 , GBC 60 , BRCA 74 , NSCLC 32 and GBM 75 , suggesting that MTDH was defined as a clinical and prognostic biomarker in various cancers, and through detection of MTDH expression, timely diagnosis of cancer patients in early stage may be possible.…”
Section: Clinical and Prognostic-biomarkermentioning
confidence: 99%
“…Meanwhile, high expression of MTDH was associated with distant metastasis of colorectal cancer and survival of patients after surgery. Moreover, based on clinical patient samples, a large number of studies have found that high expression of MTDH was significantly associated with postoperative survival rate, tumor metastasis, clinical stage progression and tumor angiogenesis in HCC 73 , GBC 60 , BRCA 74 , NSCLC 32 and GBM 75 , suggesting that MTDH was defined as a clinical and prognostic biomarker in various cancers, and through detection of MTDH expression, timely diagnosis of cancer patients in early stage may be possible.…”
Section: Clinical and Prognostic-biomarkermentioning
confidence: 99%